First records of holothurian predation by the ocellated eagle ray (Aetobatus ocellatus) in Réunion island - Estelle Crochelet; Océane Desbonnes; Jean-Pascal Quod; Thierry Mulochau (Environmental Biology of Fishes, 2026)

Spread of a sea urchin disease to the Indian Ocean causes widespread mortalities—Evidence from Réunion Island - Jean‐Pascal Quod; Mathieu Séré; Ian Hewson; Lachan Roth; Omri Bronstein (Ecology, 2025)

First Records of a Hydrolagus Species (Holocephali: Chimaeridae) from Reunion Island and Mayotte (Southwestern Indian Ocean) - Bernard Séret; Jean-Pascal Quod (Fishes, 2023)
Two specimens of large blackish chimaeras of the genus Hydrolagus were caught, one off Reunion Island and the other off Mayotte in the southwestern Indian Ocean. The specimens, an adult male of 710 mm BDL and a female of 870 m BDL, are described, compared to similar species (i.e., having a large size, over 110 cm TL, dark blackish colour, and rather long conical snout), and tentatively identified to the small-eyed rabbitfish Hydrolagus affinis, pending a taxonomic revision of the large blackish chimaeras is completed.

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Stingrays as possible facilitators for foraging trevallies in a nearshore sandflat - Jeremy J. Kiszka; Michael R. Heithaus; Jean-Pascal Quod (Marine Biodiversity, 2015)

Identification of a bacterial pathogen associated with Porites white patch syndrome in the Western Indian Ocean - Mathieu G. Séré; Pablo Tortosa; Pascale Chabanet; Jean‐Pascal Quod; Michael J. Sweet; Michael H. Schleyer (Molecular Ecology, 2015)
Porites white patch syndrome ( PWPS ) is a coral disease recently described in the Western Indian Ocean. This study aimed to isolate and identify potential pathogens associated with PWPS utilizing both culture and nonculture screening techniques and inoculation trials. A total of 14 bacterial strains (those dominant in disease lesions, absent or rare in healthy tissues and considered potential pathogens in a previous study) were cultured and used to experimentally inoculate otherwise healthy individuals in an attempt to fulfil Henle–Koch's postulates. However, only one (P180R), identified as closely related (99–100% sequence identity based on 1.4 kb 16S RNA sequence) to Vibrio tubiashii , elicited signs of disease in tank experiments. Following experimental infection (which resulted in a 90% infection rate), the pathogen was also successfully re‐isolated from the diseased tissues and re‐inoculated in healthy corals colonies, therefore fulfilling the final stages of Henle–Koch's postulates. Finally, we report that PWPS appears to be a temperature‐dependent disease, with significantly higher tissue loss ( anova : d.f. = 2, F = 39.77, P 2 per day (mean ± SE)] compared to ambient temperatures of 28 and 26 °C (0.73 ± 0.80 cm 2 per day (mean ± SE ) and 0.51 ± 0.50 cm 2 per day (mean ± SE ), respectively).

Mass-settlement of the Indian ocean black-tip grouper Epinephelus oceanicus (Lacepède, 1802) in a shallow volcanic habitat following a tropical storm - Mathieu Pinault; Jean-Pascal Quod; René Galzin (Environmental Biology of Fishes, 2015)